Mandela : long walk to freedom - Chadwick, Justin; Nicholson, William; Elba, Idris; Harris, Naomie; Kgoroge, Tony; Moosa, Riaad; Matshikiza, Lindiwe; Distant Horizon ([place of publication not identified] : [publisher not identified], 2013)
Nelson Mandela (Idris Elba) is a South Africa lawyer who joins the African National Congress in the 1940s when the law under the Apartheid system's brutal tyranny proves useless for his people. Forced to abndon peaceful protest for armed resistance after the Sharpeville Massacre, Mandela pays the price when he and his comrades are sentenced to life imprisonment for treason while his wife, Winnie, is abused by the authorities herself. Over the decades in chains, Mandela's spirit is unbowed as his struggle goes on in and beyond his captivity to become an international cause. However, as Winnie's determination hardens over the years into a violent ruthlessness, Nelson's own stature rises until he becomes the renowned leader of his movement. That status would be put to the test as his release nears and a way must be found to win a peaceful victory that will leave his country, and all its peoples, unstained.
Based on Nelson Mandela's autobiography'Long Walk to Freedom'.
Director of photography, Lol Crawly ; production designer, Johnnt Breedt ; editor, Rick Russell ; music by Alex Heffes ; executive producers, Cameron McCracken, Francois Ivernel, Geoffrey Qhena, Basil Ford, Philisiwe Mthethwa, Harvey Weinstein, Sudhir Pragjee, Sanjeev Singh.
Idris Elba, Naomie Harris, Tony Kgoroge, Riaad Moosa, Lindiwe Matshikiza.
DVD format, MPEG 2, PAL, Region 3, Surround 5.1.
In English with optional Malay and Chinese subtitles.
Title from title screen.
Keywords: Mandela, Nelson, -- 1918-2013 -- Drama; Mandela, Nelson, -- 1918-2013 -- Film adaptations; Presidents -- South Africa -- Drama; Anti-apartheid activists -- South Africa -- Drama; Biographical films